The effect of seed harvesting time on emergence indices, physiological characteristics, yield and yield components of borage (Borago officinalis L.) - Mahrokh Bolandi; Parisa Sheikhzadeh Mosaddegh; Saeed Khomari; Nasser Zare; Jaber Sharifi (علوم و فناوری بذر ایران, 2023)
To investigate the effect of different stages of seed maturity at the time of harvest, on emergence indices, physiological and functional characteristics of borage, the seeds of maternal plant were used and an experiment was carried out in a randomized complete block design with three replications at the University of Mohaghegh Ardabili. The experimental treatment was the different stages of maturation of the seeds of the maternal plants at the time of harvesting, which were harvested from the maternal plants at three times (23, 32 and 38 days after flowering). The results showed that the effect of maturation stages at the time of seed harvesting from maternal plants on all measured traits (emergence indices, photosynthetic pigments of chlorophyll, secondary metabolites and grain yield components) was significant. The seeds obtained from the second stage of seed harvesting (32 days after flowering), due to the favorable maturation of seeds, with an increase in the percentage and rate of germination, improvement in the growth and rapid establishment of the plants, an increase in the amount of photosynthetic pigments of chlorophyll and the formation of a favorable plant density in the field, compared to the two masses of seeds obtained from the first and third stages of seed harvesting, had the greatest effect on increasing flower yield, grain yield, 1000-seed weight and other components of Grain yield. The highest amount of phenol and flavonoid was observed at the time of planting the seeds with harvest time 38 days after flowering,